Verbalization, Categorization, and Evaluation of Fundamental Surgical Skills: An Expert Consensus in Open Head and Neck Surgery. Issue 2 (7th June 2021) - Mitani, Sohei; Nishio, Naoki; Kitani, Takashi; Ugumori, Toru; Wakisaka, Hiroyuki; Tanaka, Keiko; Miao, Beiping; Chan, Jason Y. K.; Holsinger, F. Christopher; Hato, Naohito
Abstract : Objective: This study aimed to verbalize fundamental surgical skills required for open head and neck surgery (OHNS), to organize them by categorization, and to establish a consensus among surgeons regarding the importance and difficulty of each skill. Summary Background Data: Improvement of fundamental surgical skills is the core of surgical education; however, surgical skills are not yet organized, and consensus in any surgical field remains uncertain. Methods: Fundamental surgical skills during OHNS were collected from surgical textbooks, real surgeries, and expert interviews. The items were analyzed to calculate the frequency of words and were categorized by 2 expert surgeons. After consensus on the importance and difficulty of each item was established by 15 expert surgeons using a Delphi survey, principal component (PC) analysis was performed to integrate importance and difficulty into a single parameter. Results: Sixty skills were verbalized and categorized into 7 categories: "skin flap elevation (n = 6), " "vessel management (n = 9), " "nerve preservation (n = 8), " "instrument handling (n = 11), " "counter traction (n = 7), " "tissue exposure (n = 9), " and "flow and planning (n = 10)." In the Delphi survey, expert consensus was established after 2 voting rounds (Cronbach's α ≥ 0.80). The "counter traction" and "flow and planning" categories had high PC scores, which indicate priority in surgical education. Conclusion: Fundamental OHNS skills were verbalized, categorized, and evaluated via expert consensus. Assessment of surgeons' skills by the structured items hereby developed will help standardize the quality of OHNS and improve patient outcomes. Abstract : Fundamental open head and neck surgery skills were verbalized, categorized, and evaluated via expert consensus. This can facilitate the evaluation of surgical skills and lead to the standardization of the quality of these surgeries and improvement of patient outcomes. Supplemental Digital Content is available in the text.